2016
DOI: 10.1145/2948072
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Finance Keywords via Continuous-Space Language Models

Abstract: The growing amount of public financial data makes it increasingly important to learn how to discover valuable information for financial decision making. This article proposes an approach to discovering financial keywords from a large number of financial reports. In particular, we apply the continuous bag-of-words (CBOW) model, a well-known continuous-space language model, to the textual information in 10-K financial reports to discover new finance keywords. In order to capture word meanings to better locate fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…However, concern can be replaced with pertain only if it does not have any sentiment polarity. It can be seen that expanding the lexicon using word embeddings, like previous works did (Tsai and Wang, 2014;Tsai et al, 2016;Rekabsaz et al, 2017), can be problematic and may end up with a lexicon expansion contain- ing semantically close but sentimentally far words. Another interesting word in the list is DMAA.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, concern can be replaced with pertain only if it does not have any sentiment polarity. It can be seen that expanding the lexicon using word embeddings, like previous works did (Tsai and Wang, 2014;Tsai et al, 2016;Rekabsaz et al, 2017), can be problematic and may end up with a lexicon expansion contain- ing semantically close but sentimentally far words. Another interesting word in the list is DMAA.…”
Section: Discussionmentioning
confidence: 96%
“…Stemming decreases the vocabulary size of the word embeddings and thus reduces the parameters of the model. Stemming is also required to use word vectors trained by Tsai et al (2016) since the corpora which is used to train the word embeddings consists of stemmed reports.…”
Section: Preprocessingmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that doing so both improves the performance of a Ranking Support Vector Machine (SVM rank ) as well as a Support Vector Regression (SVR) model with bag-of-word vectors as features and stock return volatility in the year after the filing date as label. Following up, Tsai et al [33] show that such an expanded dictionary can effectively be used to not only predict return volatility, but also post-event volatility (estimated with the Fama-French 3-factor model [7]) in the following year. Although the authors acknowledge that the regression on post-event volatility is sensitive with regard to the number of added candidates k [33, cf.…”
Section: Natural Language Processing Literaturementioning
confidence: 99%